IMF Staff Papers : Volume 10, No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1963)
This paper describes the operations of the international monetary system and to evaluate its efficacy to meet existing and foreseeable problems. The attempt is made to put the essential characteristics of the entire monetary system in a realistic perspective and to lay a better basis for studying and evaluating problems importantly affected by the operations of the system. Thus, the present international payments system is a deliberate choice among the means of conducting international financial relations. It is not rigid, and it makes provision for both adapting to enduring changes and meeting sudden and grave financial crises. However, the system has two permanent features-the use of par values and the convertibility of currencies for current transactions; without these features, it would cease to exist. The measures taken will be dealt with in a subsequent article on the management of the convertibility system and the techniques available for its defense.